Prednisolone and tacrolimus versus prednisolone and cyclosporin A to treat polymyositis/dermatomyositis‐associated ILD: A randomized, open‐label trial. Issue 4 (11th November 2020) - Fujisawa, Tomoyuki; Hozumi, Hironao; Kamiya, Yosuke; Kaida, Yusuke; Akamatsu, Taisuke; Kusagaya, Hideki; Satake, Yasuomi; Mori, Kazutaka; Mikamo, Masashi; Matsuda, Hiroyuki; Yokomura, Koshi; Koshimizu, Naoki; et al.
ABSTRACT: Background and objective: The efficacy of combination therapy with corticosteroids and CNI, TAC and CsA, for PM/DM‐ILD has been described retrospectively. However, it remains unknown which CNI treatment regimens, TAC or CsA regimens, are more effective as initial treatments for patients with PM/DM‐ILD. Methods: We conducted a prospective multicentre, open‐label, randomized, 52‐week phase 2 trial. Patients with PM/DM‐ILD were randomly allocated to receive PSL plus TAC (TAC group) or PSL plus CsA (CsA group). The primary endpoint was PFS rate in the intention‐to‐treat population at 52 weeks. The secondary endpoints were OS rate at 52 weeks, changes in pulmonary function tests from baseline to 52 weeks and AE. Results: Fifty‐eight patients were randomly assigned to the TAC group ( n = 30) and the CsA group ( n = 28). The PFS rates at 52 weeks were 87% in the TAC group and 71% in the CsA group ( P = 0.16). The OS rates at 52 weeks were 97% in the TAC group and 93% in the CsA group ( P = 0.50). The %FVC at 52 weeks in the per‐protocol populations significantly increased in both groups. None of the patients discontinued the treatment due to AE. Conclusion: PSL plus TAC treatment may achieve a better short‐term PFS rate compared with PSL plus CsA treatment. Further studies must be conducted to evaluate the long‐term efficacy and safety of such treatment. Abstract : This is the first prospective trial to compare the efficacy of two different regimens, PSL plus TAC and PSL plus CsA, in patients with PM/DM‐ILD. PSL plus TAC may achieve a better progression‐free survival rate at 52 weeks than PSL plus CsA.